Narrativas sobre a formação de um professor espect-a(u)tor eco-relacional: ser-estar com o outro e com o mundo - Leão, Fernando Antônio Fontenele (2023)
We are experiencing a multifaceted crisis of humanity, which has prevented us from imagining the future as something better than the present. This crisis also convinces us that the Other – the different – can be a burden or even represent a threat, and the best thing is for each person to just take care of themselves, to individualize themselves, even if the cost of this is a life without stories, without experiences, without loves. The Eco-Relational Perspective, which supports this thesis, denounces the crisis and announces other possible, complex readings that reorient us towards the dream, in the search for a more beautiful, more colorful, more plural, more collective world in which it is “less difficult to love”. Experiencing this in theater teacher training can lead to a specific professional profile, which I have called espect-a(u)tor ecorelacional teacher. The thesis is that a process of training theater teachers, based on dimensions referenced in the thoughts of Paulo Freire and Augusto Boal, in conjunction with the Eco- Relational Perspective, is capable of training a teaching professional endowed with a conscious body, able to observe, feel, reflect, create and act, considering criticality, dialogicity, lovingness and autonomy, as a way of being with others and with the world. The thesis has the general objective present paths for the training of the espect-a(u)tor eco-relacional teacher. For that, it has three specific objectives: a) explain the genesis of the proposed profile; b) identify the structuring dimensions of training for this profile; c) characterize the teacher's pedagogical praxis, which shapes the other's thinking while working. This is qualitative work, within the framework of the autobiographical method applied to teacher training, considering the researchtraining paradigm, which consists of constructing narratives in which the author-narrator assumes his own experiences as an object of reflection and study. As a result, the thesis has a summary table of the profile of an espect-a(u)tor eco-relacional teacher, with emphasis on the four dimensions of teacher training – artistic-aesthetic, didactic- pedagogical, ethical-political and affective-relational –, presented from autobiographical narratives and theoreticalmethodological reflections on each of the dimensions.